Pieśni bólu i rozpaczy. O "Pieśniach północnych" (1973) Andrzeja Krzanowskiego - Stochniol, Magdalena (Res Facta Nova, 2021)
Andrzej Krzanowski’s compositions, particularly those written at the beginning of his creative journey, are still sidelined by researchers and performers. The article describes his Pieśni północne [Northern songs] (1973) for eight-voice mixed choir a cappella, to words by Kazimierz Ratoń, composed while he was a student in the class of Henryk Mikołaj Górecki. The axis of interpretation is provided by two strands: the meaning of the text and its relationship with the musical means of expression, as well as selected musical aspects such as scales, form and references to other compositions.